A Qualitative Study Related Influence of Personality Contribution of Executives to Their Jobs on Job Satisfaction - Kazanci, Onur (International Journal of Contemporary Economics and Administrative Sciences, 2023)
People currently spend much of their most productive time at work place. Due to recent remote work and similar processes made possible by sophisticated developments in information technologies, it would not be wrong to to suggest that employees have been in interaction with their job for 24/7. Therefore feelings of employees about their job consist areas of research, one of which is job satisfaction. Although there is a a variety of approaches to relationships between job satisfaction and work performance, what is generally accepted is that job satisfaction influences both individual and organizational work performances/ satisfaction. Likewise, numerous factors with impacts on job satisfaction exist. The current study examined influences of Personality Contribution to Job of top managers and executives. The consequences of the research on face to face interview with thirty executives indicated that job satisfaction tended to create different impacts on managers who have status and managerial experiences in organizations of different industries.